Atmospheric entry of sub-millimetre-sized grains into Mars atmosphere: white soft mineral micrometeoroids. Issue 5 (1st October 2022) - Micca Longo, Gaia; Longo, Savino
Abstract: In this work, we study the passage through the Martian atmosphere of micrometeorites with a white soft mineral (WSM) composition, which have been proposed as transporters of organic molecules in the solar system. The atmospheric entry model includes the dynamics of the atmospheric entry and the physico-chemical aspects of the thermal decomposition process. The results show that, due to the reduced entry speed, Mars may have been a promising collector of matter in this form. In particular, the chemical decomposition process is much more effective than in the case of the Earth's atmosphere in maintaining a moderate temperature of the micrometeorite during most of the entry process.